2020
DOI: 10.1016/j.akcej.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Status connectivity indices and co-indices of graphs and its computation to some distance-balanced graphs

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Please cite this article in press as: H.S. Ramane, et al., Status connectivity indices and co-indices of graphs and its computation to some distance-balanced graphs, AKCE International

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Recently, the hyper Gourava indices were studied in [6]. Recently, some variants of status indices were introduced and studied such as first and second status connectivity indices [7], first and second hyper status indices [8], F 1 -status index [9], harmonic status index [10], multiplicative vertex status index [11], (a, b)-status index [12], status connectivity coincides [13]. Recently, some different multiplicative indices were studied, for example, in [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the hyper Gourava indices were studied in [6]. Recently, some variants of status indices were introduced and studied such as first and second status connectivity indices [7], first and second hyper status indices [8], F 1 -status index [9], harmonic status index [10], multiplicative vertex status index [11], (a, b)-status index [12], status connectivity coincides [13]. Recently, some different multiplicative indices were studied, for example, in [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Where a is a real number. Some of the research works on status indices can be found in [12,13,14,15].In this paper, the values of these newly proposed indices for unitary cayley graphs are determined.…”
mentioning
confidence: 99%